Polyarylene sulfide resin composition, molded article, composite, and method for producing same

By blending carbon-based materials at a specific pH value with low melt viscosity polyaroyl sulfides, a composite material with high conductivity, high toughness and long-term stability is solved, and the problem of difficulty in achieving these properties simultaneously in the prior art is solved.

JP7648016B1Active Publication Date: 2025-03-18DIC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024563095
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2024-07-25
Publication Date
2025-03-18
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both high conductivity, high toughness and long-term stability in battery electrode assemblies.

Method used

By blending carbon-based materials with specific pH values ​​(except fibers) with polyaroyl sulfide (PAS) with a melt viscosity of no more than 200 Pa·s, composite materials with excellent conductivity, toughness and long-term stability were prepared.

Benefits of technology

It has achieved a comprehensive improvement in electrical conductivity, toughness and long-term stability of composite materials, and is suitable for applications such as lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648016000001
    Figure 0007648016000001
  • Figure 0007648016000002
    Figure 0007648016000002
  • Figure 0007648016000003
    Figure 0007648016000003
Patent Text Reader

Abstract

The present invention provides a resin composition, a molded article, and a composite having excellent electrical conductivity, toughness, processability, and long-term stability, and methods for producing the same. More specifically, the present invention provides a PAS resin composition comprising a polyarylene sulfide (hereinafter, PAS) resin (A) and a carbon-based material other than carbon fiber (B) as essential components, wherein the melt viscosity (V6) of the PAS resin (A) is 200 Pa s or less, the pH of the carbon-based material other than carbon fiber (B) is 6 or more, the blending amount of the carbon-based material other than carbon fiber (B) is 5 to 80 parts by mass per 100 parts by mass of the PAS resin (A), and the flexural modulus of elasticity is 18 GPa or less, and methods for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyarylene sulfide resin composition, a polyarylene sulfide resin molded article, a resin-metal composite, and methods for producing them. [Background technology]

[0002] In recent years, the demand for secondary batteries such as lithium-ion batteries (LiBs) has been increasing with the promotion of vehicle electrification and the spread of renewable energy. Electrode components for LiBs are required to have appropriate electrical conductivity, small variation in electrical conductivity, toughness, and reliability during long-term use (long-term stability).

[0003] On the other hand, polyarylene sulfide (hereinafter sometimes abbreviated as "PAS") resins, such as polyphenylene sulfide (hereinafter sometimes abbreviated as "PPS") resin, are widely used mainly in electrical and electronic equipment parts and automotive parts materials because of their excellent mechanical strength, heat resistance, chemical resistance, moldability, dimensional stability, and flame retardancy.

[0004] Since PAS resin is an insulating material, it needs to be made conductive in order to be used in the anode safety parts of LiBs, and the general method is to compound it with conductive materials such as carbon fiber or carbon black.In addition, since it is used by joining with metal parts, it is required to have high toughness from the viewpoint of adhesion to the parts.

[0005] As a conventional PAS resin composition for LiB, for example, Patent Document 1 discloses a PPS resin composition containing PAS resin, graphite, carbon fiber, and polyolefin wax, and Patent Document 2 discloses a resin composition containing PPS, conductive carbon black, carbon fiber, and graphite. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2006-19227 A [Patent Document 2] International Publication No. 2002 / 093670 Brochure Summary of the Invention [Problem to be solved by the invention]

[0007] However, the required properties are becoming increasingly high, and there are cases where conventional materials are not sufficient to meet these requirements. In particular, there is a demand for small variations in electrical conductivity and suppression of deterioration during long-term use, and it has been difficult to achieve these properties together with high electrical conductivity and toughness.

[0008] Therefore, an object of the present invention is to provide a PAS resin composition, a molded article and a composite material, which are excellent in electrical conductivity, toughness, processability and long-term stability, and a method for producing the same. [Means for solving the problem]

[0009] As a result of intensive research aimed at solving the above-mentioned problems, the inventors discovered that a resin composition which solves the above-mentioned problems can be obtained by blending a specific amount of a carbon-based material other than carbon fiber having a specific pH with a PAS resin having a melt viscosity of 200 Pa s or less, and thus completed the present invention.

[0010] That is, the present disclosure provides a PAS resin composition comprising a PAS resin (A) and a carbon-based material (B) other than carbon fiber as essential components, The melt viscosity (V6) of the PAS resin (A) is 200 Pa s or less, The pH of the carbon-based material (B) other than the carbon fiber is 6 or more, The blending amount of the carbon-based material (B) other than the carbon fiber is 5 to 80 parts by mass relative to 100 parts by mass of the PAS resin (A), and The present invention relates to a PAS resin composition having a flexural modulus of 18 GPa or less.

[0011] The present disclosure also relates to a PAS resin molded article obtained by molding the above-described PAS resin composition.

[0012] The present disclosure also relates to a composite member obtained by joining the above-described molded article to a metal member.

[0013] The present disclosure also provides a method for producing a PAS resin composition, comprising a step of blending a PAS resin (A) and a carbon-based material (B) other than carbon fiber as essential components, and melt-kneading the mixture at a temperature equal to or higher than the melting point of the PAS resin (A), The melt viscosity (V6) of the PAS resin (A) is 200 Pa s or less, The pH of the carbon-based material (B) other than the carbon fiber is 6 or more, The blending amount of the carbon-based material (B) other than the carbon fiber is 5 to 80 parts by mass relative to 100 parts by mass of the PAS resin (A), and The present invention relates to a method for producing a PAS resin composition having a flexural modulus of 18 GPa or less.

[0014] The present disclosure also relates to a method for producing a molded article, comprising the steps of producing a PAS resin composition by the above-described production method and melt-molding the resulting PAS resin composition.

[0015] The present disclosure also relates to a method for producing a composite, comprising the steps of producing a molded article by the above-described production method, and joining the obtained molded article to a metal member. Effect of the Invention

[0016] According to the present invention, it is possible to provide a resin composition, a molded article, and a composite material, which are excellent in electrical conductivity, toughness, processability, and long-term stability, as well as methods for producing these. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, embodiments of the present invention will be described in detail. However, the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without departing from the spirit of the present invention. Further, when a plurality of upper limit values and lower limit values are described for specific parameters, any upper limit value and lower limit value can be combined to form a suitable numerical range.

[0018] The PAS resin composition according to this embodiment is a PAS resin composition prepared by blending a PAS resin (A) and a carbon-based material (B) other than carbon fiber as essential components. The melt viscosity (V6) of the PAS resin (A) is 200 Pa·s or less. The pH of the carbon-based material (B) other than carbon fiber is 6 or more. The blending amount of the carbon-based material (B) other than carbon fiber is 5 to 80 parts by mass with respect to 100 parts by mass of the PAS resin (A), and It is characterized in that the flexural modulus is 18 GPa or less. The following will be described.

[0019] <PAS resin (A)> The PAS resin composition according to this embodiment is prepared by blending a PAS resin (A) as an essential component.

[0020] The PAS resin has a resin structure having a structure in which an aromatic ring and a sulfur atom are bonded as a repeating unit. Specifically, the following general formula (1)

[0021]

Chemical formula

[0022]

Chemical formula

[0023] Here, the structural portion represented by the general formula (1) is particularly R 1 and R 2 is preferably a hydrogen atom from the viewpoint of the mechanical strength of the PAS resin, and in that case, examples include those bonded at the para position represented by the following formula (3) and those bonded at the meta position represented by the following formula (4).

[0024] [ka] Among these, a structure in which the bond between the sulfur atom and the aromatic ring in the repeating unit is at the para position represented by the general formula (3) is particularly preferred in terms of the heat resistance of the PAS resin.

[0025] The PAS resin may include not only the structural moieties represented by the general formula (1) or (2) but also the structural moieties represented by the following structural formulae (5) to (8):

[0026] [ka] The structural moiety represented by the general formula (1) and the structural moiety represented by the general formula (2) may be contained in an amount of 30 mol % or less of the total of the structural moieties represented by the general formula (1) and the general formula (2). In particular, in the present disclosure, it is preferable that the structural moieties represented by the general formulae (5) to (8) are 10 mol % or less in terms of the heat resistance and mechanical strength of the PAS. When the structural moieties represented by the general formulae (5) to (8) are contained in the PAS resin, the bonding mode thereof may be either a random copolymer or a block copolymer.

[0027] The PAS resin may have naphthyl sulfide bonds or the like in its molecular structure, but the amount of such bonds is preferably 3 mol % or less, and particularly preferably 1 mol % or less, relative to the total number of moles including other structural portions.

[0028] The physical properties of the PAS resin (A) are not particularly limited as long as they do not impair the effects of the present invention, but are as follows.

[0029] (Melt Viscosity) The melt viscosity (V6) of the PAS resin (A) used in this embodiment is in the range of 200 Pa·s or less when measured at 300°C, since this provides a good balance between processability and toughness. It is preferably in the range of 2 Pa·s or more, and more preferably in the range of 30 Pa·s or more. It is preferably in the range of 180 Pa·s or less, and more preferably in the range of 160 Pa·s or less. However, the melt viscosity (V6) of the PAS resin is measured using a Shimadzu flow tester, CFT-500D, at 300°C, load: 1.96×10 6 The melt viscosity is measured after holding the sample for 6 minutes at a pressure of 1 Pa and L / D = 10 (mm) / 1 (mm).

[0030] (Non-Newtonian Exponents) The non-Newtonian index of the PAS resin (A) used in this embodiment is not particularly limited, but is preferably in the range of 0.90 or more to 2.00 or less. When a linear PAS resin is used, the non-Newtonian index is preferably in the range of 0.90 or more, more preferably 0.95 or more, and preferably 1.50 or less, more preferably 1.20 or less. Such a PAS resin has excellent mechanical strength and flowability. However, in this disclosure, the non-Newtonian index (N value) is a value calculated using the following formula by measuring the shear rate (SR) and shear stress (SS) using a capillograph under the conditions of melting point +20°C and the ratio of the orifice length (L) to the orifice diameter (D) L / D=40. The closer the non-Newtonian index (N value) is to 1, the closer the structure is to a linear structure, and the higher the non-Newtonian index (N value), the more branched the structure is.

[0031]

number

[0032] (Carboxyl group content) The carboxyl group content of the PAS resin (A) used in this embodiment is preferably in the range of 10 μmol / g or more to 200 μmol / g or less, more preferably in the range of 20 μmol / g or more to 180 μmol / g or less. In this range, the resin composition can have good processability and can obtain a molded product with excellent long-term stability. In this disclosure, the carboxyl group content is a value measured by the method described in the examples.

[0033] (Zeta potential) The PAS resin (A) used in this embodiment preferably has a zeta potential of -70 mV or more, more preferably -50 mV or more, measured by a streaming potential method under conditions of pH 7.8 to 8.2. The zeta potential of the PAS resin is a value measured using a film made of the PAS resin as a test piece, in an electrolyte: a 1 mmol / L KCl aqueous solution, at a measurement temperature of 22 to 26°C, using SurPASS3 (Anton Paar). The zeta potential refers to the average value of three measurements of the zeta potential on the surface of the test piece.

[0034] (Manufacturing method) The method for producing the PAS resin is not particularly limited, but examples thereof include (Production Method 1) a method in which a dihalogenoaromatic compound is polymerized in the presence of sulfur and sodium carbonate, and if necessary, a polyhalogenoaromatic compound or other copolymerization component is added, (Production Method 2) a method in which a dihalogenoaromatic compound is polymerized in a polar solvent in the presence of a sulfidizing agent or the like, and if necessary, a polyhalogenoaromatic compound or other copolymerization component is added, (Production Method 3) a method in which p-chlorothiophenol is added, and if necessary, other copolymerization components are added, and self-condensation is performed, and (Production Method 4) a method in which a diiodoaromatic compound and elemental sulfur are melt-polymerized under reduced pressure in the presence of a polymerization inhibitor that may have a functional group such as a carboxyl group or an amino group. Among these methods, (Production Method 2) is preferred because it is versatile. During the reaction, an alkali metal salt of a carboxylic acid or sulfonic acid or an alkali hydroxide may be added to adjust the degree of polymerization. Among the above-mentioned (Production Method 2) methods, there is a method for producing a PAS resin by introducing a water-containing sulfidizing agent into a mixture containing a heated organic polar solvent and a dihalogeno aromatic compound at a rate at which water can be removed from the reaction mixture, and reacting the dihalogeno aromatic compound and the sulfidizing agent in the organic polar solvent, and optionally adding a polyhalogeno aromatic compound, and controlling the amount of water in the reaction system to within a range of 0.02 to 0.5 mol per mol of the organic polar solvent (see JP-A-07-228699). Particularly preferred is a method in which a dihalogenoaromatic compound and, if necessary, a polyhalogenoaromatic compound or other copolymerization component are added in the presence of an alkali metal sulfide and an aprotic polar organic solvent, and an alkali metal hydrosulfide and an organic acid alkali metal salt are reacted while controlling the organic acid alkali metal salt in the range of 0.01 to 0.9 mol per mol of the sulfur source and the amount of water in the reaction system to be 0.02 mol or less per mol of the aprotic polar organic solvent (see WO2010 / 058713 pamphlet).Specific examples of the dihalogenoaromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-di Examples of the polyhalogeno aromatic compounds include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, 1,4,6-trihalonaphthalene, etc. The halogen atoms contained in the above compounds are preferably chlorine atoms or bromine atoms.

[0035] The method for post-treating the reaction mixture containing the PAS resin obtained by the polymerization step is not particularly limited, but for example, (post-treating 1) after the completion of the polymerization reaction, first, the solvent is distilled off under reduced pressure or normal pressure, either as is or after the addition of an acid or base, and then the solid matter remaining after the solvent distillation is washed once or twice or more times with a solvent such as water, the reaction solvent (or an organic solvent having a similar solubility to the low molecular weight polymer), acetone, methyl ethyl ketone, or alcohols, and then neutralized, washed with water, filtered, and dried; or (post-treating 2) after the completion of the polymerization reaction, the reaction mixture is dissolved in a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, or aliphatic hydrocarbons (soluble in the polymerization solvent used and poorly soluble in at least PAS). or (post-treatment 3) a method in which, after the polymerization reaction is completed, a reaction solvent (or an organic solvent having a solubility equivalent to that of the low molecular weight polymer) is added to the reaction mixture, the mixture is stirred, the mixture is filtered to remove the low molecular weight polymer, the mixture is washed once or twice with a solvent such as water, acetone, methyl ethyl ketone, or alcohols, and the mixture is neutralized, washed with water, filtered, and dried; (post-treatment 4) a method in which, after the polymerization reaction is completed, water is added to the reaction mixture, the mixture is washed with water, filtered, and if necessary, an acid is added during the water washing to perform an acid treatment, and the mixture is dried; or (post-treatment 5) a method in which, after the polymerization reaction is completed, the reaction mixture is filtered, and if necessary, the mixture is washed once or twice or more with the reaction solvent, and the mixture is washed with water, filtered, and dried. Among these methods, the method (post-treatment 4) is preferred because it can obtain a PAS resin having a carboxyl group at the molecular end of the PAS resin.

[0036] In the post-treatment methods exemplified above in (Post-treatment 1) to (Post-treatment 5), the PAS resin may be dried in a vacuum, or in air or in an inert gas atmosphere such as nitrogen.

[0037] In the PAS resin composition according to the present embodiment, the amount of the PAS resin (A) is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and preferably 80 parts by mass or less, more preferably 70 parts by mass or less, based on 100 parts by mass of the resin composition. In this range, the resin composition has good processability, and the molded product has excellent chemical resistance, toughness, etc., which is preferable.

[0038] In addition, the PAS resin (A) used in this embodiment may be a PAS resin newly polymerized by the above method, or a recycled PAS resin. For example, a PAS resin recovered from a PAS resin composition or a PAS resin molded product may be used. Specifically, a PAS resin obtained by heating a PAS resin composition or a PAS resin molded product in an organic polar solvent to dissolve the PAS contained therein and performing the above-mentioned post-treatment on the solution may be used. In addition, a PAS resin composition or a PAS resin molded product mechanically crushed may be used as the PAS resin. Specifically, a sprue or runner generated during the manufacture of a molded product, a product recovered as a non-standard molded product, or a molded product once used as a product may be crushed. In that case, a crushed product of a PAS resin composition or a PAS resin molded product containing a component other than the PAS resin may be used, but from the viewpoint of mechanical strength, the PAS resin content is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, and even more preferably 98 parts by mass or more.

[0039] <Carbon-based materials other than carbon fiber (B)> The PAS resin composition according to the present embodiment is composed of a carbon-based material (B) other than carbon fiber as an essential component. In the present disclosure, the carbon fiber is included in the fibrous filler (C) and is not included in the carbon-based material (B).

[0040] The carbon-based material (B) other than carbon fiber that can be applied to this embodiment is not particularly limited as long as it is a carbon-based material other than carbon fiber, and known materials can be used. For example, carbon black such as furnace black, thermal black, channel black, ketjen black, gas black, oil black, and acetylene black; graphite such as clay-like graphite, spherical graphite, scaly graphite, swollen graphite, and expanded graphite; carbon nanotubes such as single-wall nanotubes and multi-wall nanotubes; and fullerene. The graphite may be either natural graphite or artificial graphite, and the shape is not limited. In addition, carbon nanotubes can generally be manufactured by laser ablation, arc thermal CVD, plasma CVD, gas phase, and combustion methods, but carbon nanotubes manufactured by any method can be used in the present disclosure. In addition, the surface and end of the carbon nanotube may be modified with a functional group to increase the affinity with the resin, as long as the effect of the present invention is not impaired, and may be functionalized with a hydroxyl group, a carboxyl group, or an amino group by an acid or alkali. Furthermore, the carbon nanotubes may be pretreated with a coupling agent before use, and examples of such coupling agents include isocyanate compounds, organic silane compounds, organic titanate compounds, epoxy compounds, etc. Among these, from the viewpoint of the stability of electrical conductivity, carbon black is preferred, and furnace black is particularly preferred.

[0041] The carbon-based material (B) other than carbon fiber that can be applied to this embodiment has a pH of 6 or more, preferably more than 6. In this range, the resin composition or molded article is less likely to corrode objects in contact with it (excellent corrosion resistance), which is preferable. The upper limit of the pH is not particularly limited, but is preferably 12 or less, more preferably 10 or less. The pH of the carbon-based material (B) other than carbon fiber is a value measured by a glass electrode pH meter in accordance with JIS K 6221 for the pH of a mixture of the carbon-based material (B) other than carbon fiber and distilled water.

[0042] Examples of commercially available carbon-based materials (B) other than carbon fibers include "CNP15" manufactured by Ito Graphite Industries Co., Ltd., "Denka Black" manufactured by Denka Co., Ltd., "3400B" manufactured by Mitsubishi Chemical Corporation, and "Ketjen Black" manufactured by Lion Specialty Chemicals Co., Ltd.

[0043] When furnace black is used as the carbon-based material (B) other than the carbon fiber, the DBP absorption is 100 cm 3 / 100g or more is preferable, 110cm 3 It is more preferable that the DBP absorption amount of furnace black is not less than 100 / 100. In this range, the balance between the electrical conductivity and the fluidity is excellent, which is preferable. The DBP absorption amount of furnace black is a value measured according to the method described in JIS K6221.

[0044] In addition, when furnace black is used as the carbon-based material (B) other than the carbon fiber, the primary particle size is preferably 60 nm or less, more preferably 50 nm or less. In this range, the balance between electrical conductivity and fluidity is excellent, which is preferable. The primary particle size is the average value measured for at least five samples by observation using a transmission electron microscope.

[0045] When graphite is used as the carbon-based material (B) other than carbon fiber, the average particle diameter is preferably 5 to 400 μm. In this range, the resin composition can exhibit excellent dispersibility. From the same viewpoint, the average particle diameter is more preferably 10 μm or more, even more preferably 15 μm or more, and more preferably 350 μm or less, even more preferably 300 μm or less. The average particle diameter is the average particle diameter (D 50 )

[0046] In the PAS resin composition according to the present embodiment, the amount of the carbon-based material (B) other than carbon fiber is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and preferably 80 parts by mass or less, more preferably 60 parts by mass or less, relative to 100 parts by mass of the PAS resin (A). In this range, the resin composition has good processability, and the molded product has excellent electrical conductivity, mechanical strength, and dimensional stability, which is preferable.

[0047] <Fibrous filler (C)> The PAS resin composition according to this embodiment may further contain a fibrous filler (C) as an optional component in order to improve mechanical strength and processability during molding. The fibrous filler (C) applicable to this embodiment is not particularly limited and may be any known filler. For example, fibrous fillers such as glass fiber, carbon fiber, silane glass fiber, ceramic fiber, aramid fiber, metal fiber, potassium titanate, silicon carbide, calcium silicate, wollastonite, and natural fibers may be used.

[0048] The fibrous filler (C) used in the present invention may be processed with a surface treatment agent or a sizing agent, if necessary. This is preferable because it can improve the adhesive strength with the PAS resin (A) and improve the mechanical strength of the resulting resin composition and molded product. Examples of the surface treatment agent or sizing agent include at least one polymer selected from the group consisting of silane compounds having functional groups such as amino groups, epoxy groups, isocyanate groups, and vinyl groups, titanate compounds, acrylic resins, urethane resins, polyether resins, and epoxy resins, and when glass fibers are used in particular, it is preferable to use one containing a urethane resin from the viewpoint of suppressing excessive defibration during processing. When the surface treatment agent or sizing agent contains a urethane resin, the content is not particularly limited, but from the viewpoint of moisture and heat resistance, it is preferably in the range of 35% by mass or less, and more preferably in the range of 20% by mass or less.

[0049] When the fibrous filler (C) is blended in the PAS resin composition according to the present embodiment, the blending amount is not particularly limited, but is preferably in the range of 20 parts by mass or more, more preferably 35 parts by mass or more, and preferably 80 parts by mass or less, more preferably 60 parts by mass or less, relative to 100 parts by mass of the PAS resin (A). In such a range, the resin composition has good processability and the molded product has excellent mechanical strength, which is preferable.

[0050] <Silane coupling agent (D)> The PAS resin composition according to this embodiment may further contain a silane coupling agent (D) as an optional component for the purposes of improving mechanical strength and reducing burrs during molding.

[0051] The silane coupling agent (D) applicable to this embodiment is not particularly limited as long as it does not impair the effects of the present invention. Preferred examples of the silane coupling agent include silane coupling agents having a functional group that reacts with a carboxyl group, such as an epoxy group, an isocyanato group, an amino group, or a hydroxyl group. Examples of such silane coupling agents include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.

[0052] In this embodiment, the silane coupling agent (D) is not an essential component, but when it is added, the amount of the silane coupling agent (D) is not particularly limited as long as it does not impair the effects of the present invention. For example, the amount is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and more preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the PAS resin (A). In this range, the resin composition has good moldability, especially releasability, and the molded product exhibits excellent adhesion to the epoxy resin while further improving mechanical strength, which is preferable.

[0053] <Thermoplastic elastomer (E)> The PAS resin composition according to this embodiment may further contain a thermoplastic elastomer (E) as an optional component for the purpose of improving mechanical strength.

[0054] Examples of the thermoplastic elastomer (E) applicable to this embodiment include polyolefin elastomers, fluorine elastomers, and silicone elastomers, among which polyolefin elastomers are preferred. When these elastomers are added, the amount of the elastomers is not particularly limited as long as it does not impair the effects of the present invention, but is preferably in the range of 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, to preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the PAS resin (A). In this range, the impact resistance of the resulting PAS resin composition is improved, which is preferable.

[0055] For example, the polyolefin-based elastomer may be a homopolymer of an α-olefin, a copolymer of two or more α-olefins, or a copolymer of one or more α-olefins and a vinyl polymerizable compound having a functional group. In this case, the α-olefin may be an α-olefin having 2 or more carbon atoms and 8 or less, such as ethylene, propylene, or 1-butene. In addition, the functional group may be a carboxyl group, an acid anhydride group (-C(=O)OC(=O)-), an epoxy group, an amino group, a hydroxyl group, a mercapto group, an isocyanate group, or an oxazoline group. Examples of the vinyl polymerizable compound having the functional group include one or more of vinyl acetate, α,β-unsaturated carboxylic acids such as (meth)acrylic acid, alkyl esters of α,β-unsaturated carboxylic acids such as methyl acrylate, ethyl acrylate, and butyl acrylate, metal salts of α,β-unsaturated carboxylic acids such as ionomers (metals include alkali metals such as sodium, alkaline earth metals such as calcium, and zinc), glycidyl esters of α,β-unsaturated carboxylic acids such as glycidyl methacrylate, and the like, α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid, and derivatives of the α,β-unsaturated dicarboxylic acids (monoesters, diesters, and acid anhydrides). The above-mentioned thermoplastic elastomers may be used alone or in combination of two or more.

[0056] The PAS resin composition according to the present embodiment may contain fillers (hereinafter referred to as other fillers) other than the carbon fiber (B) and the fibrous filler (C) as optional components within a range that does not impair the effects of the present invention. For example, fillers of various shapes such as plate-like and powder-like can be used. Specific examples include glass flakes, clay, pyrophyllite, bentonite, sericite, mica, attapulgite, ferrite, calcium silicate, zeolite, boehmite, silica, quartz powder, glass beads, glass powder, calcium silicate, aluminum silicate, diatomaceous earth and other silicates, iron oxide, titanium oxide, zinc oxide, alumina and other metal oxides, calcium carbonate, magnesium carbonate and other metal carbonates, calcium sulfate, barium sulfate and other metal sulfates, fumed silica, silicon carbide, silicon nitride, boron nitride, various metal powders, plant-derived fillers such as cacao husk and other fillers can be used.

[0057] In this embodiment, the other filler is not an essential component, but when it is blended, the blending amount is not particularly limited as long as it does not impair the effect of the present invention. The blending amount of the other filler is, for example, preferably 1 part by mass or more, more preferably 5 parts by mass or more, and preferably 600 parts by mass or less, more preferably 200 parts by mass or less, relative to 100 parts by mass of the PAS resin (A). In such a range, the resin composition shows good moldability and the molded product has excellent mechanical strength, so it is preferable.

[0058] Furthermore, in addition to the above components, the PAS resin composition according to this embodiment may further contain synthetic resins such as polyester resin, polyamide resin, polyimide resin, polyetherimide resin, polycarbonate resin, polyphenylene ether resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylate resin, polyethylene resin, polypropylene resin, polytetrafluoroethylene resin, polydifluoroethylene resin, polystyrene resin, ABS resin, epoxy resin, phenol resin, urethane resin, and liquid crystal polymer as optional components depending on the application. In particular, it is preferable to add a fluorine-based resin because it improves the sliding properties. In the present invention, the synthetic resin is not an essential component, but when it is added, the ratio of the synthetic resin is not particularly limited as long as it does not impair the effects of the present invention, and it differs depending on each purpose and cannot be generally defined, but the ratio of the synthetic resin to be added in the resin composition according to this embodiment is, for example, in the range of 5 parts by mass or more and 15 parts by mass or less relative to 100 parts by mass of the PAS resin (A). In other words, the ratio of the PAS resin to the total of the PAS resin (A) and the synthetic resin is preferably in the range of (100 / 115) or more, and more preferably in the range of (100 / 105) or more, on a mass basis.

[0059] In addition, the PAS resin composition according to the present embodiment may contain other known and commonly used additives as optional components, such as colorants, antistatic agents, antioxidants, heat stabilizers, UV stabilizers, UV absorbers, foaming agents, flame retardants, flame retardant assistants, rust inhibitors, and mold release agents (metal salts or esters of fatty acids having 18 to 30 carbon atoms, including stearic acid or montanic acid, polyolefin waxes such as polyethylene, etc.), antibacterial agents, and antiviral agents. These additives are not essential components, and may be used in an amount of, for example, preferably 0.01 parts by mass or more, and preferably 1000 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the PAS resin (A), as appropriate for the purpose and use so as not to impair the effects of the present invention.

[0060] Further, the PAS resin composition of the present disclosure is characterized in that its flexural modulus is 18 GPa or less. Preferably, it is 16 GPa or less, and more preferably 15 GPa or less. In such a range, when a PAS resin molded product is combined with a metal member, the adhesion is excellent, so that the composite member has excellent conductivity. In order to make the flexural modulus fall within such a range, for example, a method of adjusting the melt viscosity (V6) of the PAS resin within the range of 50 to 2000 Pa·s according to the content rate of the PAS resin in the resin composition can be mentioned. For example, when a large amount of components other than the PAS resin are blended, the thermal conductivity of the resin composition increases, and the crystallization rate tends to increase. Therefore, the melt viscosity of the PAS resin can be increased to adjust the crystallization behavior. Note that the method for adjusting the weld strength is not limited to the above method. Further, the flexural modulus in the present disclosure is a value of the flexural modulus measured in accordance with the measurement method of ISO 178, using a dumbbell-shaped injection molded product conforming to the type A test piece specified in ISO 20753 as the test piece, and can be measured by the method described in the examples.

[0061] <Manufacturing method of PAS resin composition> The manufacturing method of the PAS resin composition according to this embodiment is a manufacturing method of a PAS resin composition having a step of blending a PAS resin (A) and a carbon-based material (B) other than carbon fiber as essential components and melt-kneading at a temperature equal to or higher than the melting point of the PAS resin (A), wherein the melt viscosity (V6) of the PAS resin (A) is 200 Pa·s or less, the pH of the carbon-based material (B) other than carbon fiber is 6 or more, the blending amount of the carbon-based material (B) other than carbon fiber is 5 to 80 parts by mass with respect to 100 parts by mass of the PAS resin (A), and it is characterized in that the flexural modulus is 18 GPa or less. This will be described in detail below.

[0062] The method for producing a PAS resin composition according to this embodiment includes a step of blending the essential components and melt-kneading them in a temperature range equal to or higher than the melting point of the PAS resin (A). More specifically, the PAS resin composition according to this embodiment is composed of the essential components and, if necessary, other optional components. There are no particular limitations on the method for producing the resin composition used in the present invention, but examples include a method of blending the essential components and, if necessary, the optional components, and melt-kneading them, and more specifically, a method of uniformly dry-mixing them, if necessary, in a tumbler or Henschel mixer, and then feeding them into a twin-screw extruder and melt-kneading them.

[0063] The melt kneading can be carried out by heating the resin to a temperature range in which the resin temperature is equal to or higher than the melting point of the PAS resin (A), preferably equal to or higher than the melting point + 10°C, more preferably equal to or higher than the melting point + 10°C, even more preferably equal to or higher than the melting point + 20°C, preferably equal to or lower than the melting point + 100°C, more preferably equal to or lower than the melting point + 50°C.

[0064] The melt kneader is preferably a twin-screw kneading extruder from the viewpoint of dispersibility and productivity. For example, it is preferable to melt knead while appropriately adjusting the resin component discharge amount in the range of 5 to 500 (kg / hr) and the screw rotation speed in the range of 50 to 500 (rpm), and it is more preferable to melt knead under the condition that the ratio (discharge amount / screw rotation speed) is in the range of 0.02 to 5 (kg / hr / rpm). In addition, each component may be added and mixed to the melt kneader simultaneously or in portions. For example, when adding the essential component PA fiber (B) among the components and other fibrous fillers as necessary, it is preferable to feed them into the extruder from the side feeder of the twin-screw kneading extruder from the viewpoint of dispersibility. The position of the side feeder is preferably such that the ratio of the distance from the extruder resin input part (top feeder) to the side feeder to the total screw length of the twin-screw kneading extruder is 0.1 or more, more preferably 0.3 or more. Moreover, the ratio is preferably 0.9 or less, and more preferably 0.7 or less.

[0065] The PAS resin composition according to this embodiment obtained by melt-kneading as described above is a molten mixture containing the above essential components, optional components added as necessary, and their derived components. Therefore, the PAS resin composition according to this embodiment has a morphology in which the PAS resin (A) forms a continuous phase and other essential components and optional components are dispersed.

[0066] After the melt-kneading, the PAS resin composition according to this embodiment is preferably processed into forms such as pellets, chips, granules, and powders after extrusion-molding the resin composition in a molten state into strands by a known method, and then pre-dried in a temperature range of 100 to 150 °C as necessary.

[0067] <PAS resin molded article, method for manufacturing PAS resin molded article> The molded article according to this embodiment is formed by melt-molding the PAS resin composition. Further, the method for manufacturing the molded article according to this embodiment has a step of melt-molding the PAS resin composition. Therefore, the molded article according to this embodiment has a morphology in which the PAS resin (A) forms a continuous phase and other essential components and optional components are dispersed. Since the PAS resin composition has such a morphology, a molded article excellent in thermal conductivity and mechanical strength can be obtained.

[0068] The PAS resin composition according to this embodiment can be used for various moldings such as injection molding, compression molding, composite, extrusion molding such as sheet and pipe, drawing molding, blow molding, and transfer molding. In particular, it is suitable for injection molding applications because of its excellent releasability. When molding by injection molding, various molding conditions are not particularly limited, and it can be molded by a generally common method. For example, in an injection molding machine, after passing through a step of melting the PAS resin composition in a temperature range where the resin temperature is equal to or higher than the melting point of the PAS resin (A), preferably in a temperature range of the melting point + 10 °C or higher, more preferably in a temperature range of the melting point + 10 °C to the melting point + 100 °C, and even more preferably in a temperature range of the melting point + 20 to the melting point + 50 °C, it may be injected into a mold from a resin discharge port for molding. At that time, the mold temperature may also be set within a known temperature range, for example, room temperature (23 °C) to 300 °C, preferably 130 to 190 °C.

[0069] The method for producing a molded article according to this embodiment may include a step of annealing the molded article. The optimum conditions for the annealing treatment are selected depending on the application or shape of the molded article, and the annealing temperature is in a temperature range of the glass transition temperature of the PAS resin (A) or higher, preferably in a temperature range of the glass transition temperature +10°C or higher, and more preferably in a temperature range of the glass transition temperature +30°C or higher. On the other hand, it is preferably in a range of 260°C or lower, and more preferably in a range of 240°C or lower. The annealing time is not particularly limited, but is preferably in a range of 0.5 hours or higher, and more preferably in a range of 1 hour or higher. On the other hand, it is preferably in a range of 10 hours or lower, and more preferably in a range of 8 hours or lower. In such a range, not only the distortion of the molded article obtained is reduced and the crystallinity of the resin is improved, but also the thermal conductivity, mechanical strength and are further improved, which is preferable. The annealing treatment may be performed in air, but is preferably performed in an inert gas such as nitrogen gas.

[0070] The molded article according to the present embodiment includes a remolded article obtained by reusing a molded article obtained by melt-molding the PAS resin composition. Specifically, for example, the molded article includes a sprue or runner generated during the manufacture of a molded article, a molded article recovered as a non-standard molded article, or a molded article once used as a product, which is washed as necessary, crushed, and melt-molded again at a temperature equal to or higher than the melting point of the PAS resin. When reusing, it is preferable to mix the crushed molded article with the PAS resin composition from the viewpoint of mechanical strength. The size of the molded article when crushed is not particularly limited, but from the viewpoint of mixability and processability, it is preferable that the size is about the same as that of the PAS resin composition to be mixed. In addition, the mixing ratio is preferably 50 parts by mass or less of the crushed molded article relative to 100 parts by mass of the PAS resin composition, more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less. In such a range, the recyclability can be improved without impairing the effect of the PAS resin composition of the present disclosure.

[0071] <Complex and method for producing the composite> The composite according to the present embodiment is formed by bonding the molded article described above to a metal member. The method for producing the composite according to the present embodiment includes the steps of producing the molded article by the method described above and bonding the obtained molded article to a metal member.

[0072] The metal member that can be applied to this embodiment is not particularly limited as long as it does not impair the effects of the present invention, and any known metal member can be used. For example, aluminum, copper, stainless steel, magnesium, iron, titanium, or an alloy containing these may be used. More specifically, examples of the alloy include iron and, for example, stainless steel and steel, which are mainly composed of iron, i.e., 20% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass, and further contain carbon, silicon, manganese, chromium, tungsten, molybdenum, phosphorus, titanium, vanadium, nickel, zirconium, boron, etc. (hereinafter, iron alloy); aluminum and an alloy having aluminum as the main component and containing copper, manganese, silicon, magnesium, zinc, nickel, etc. (hereinafter, aluminum alloy); magnesium and an alloy having magnesium as the main component and containing zinc, aluminum, zirconium, etc. (hereinafter, magnesium alloy); copper and an alloy having copper as the main component and containing zinc, tin, phosphorus, nickel, magnesium, silicon, chromium, etc. (hereinafter, copper alloy); and titanium and an alloy having titanium as the main component and containing copper, manganese, silicon, magnesium, zinc, nickel, etc. (hereinafter, titanium alloy). Among these, iron, iron alloys, aluminum alloys, magnesium alloys, copper alloys, and titanium alloys are more preferable, and iron alloys, aluminum alloys, and magnesium alloys are further preferable. The shape of the metal member is not particularly limited, and examples thereof include those processed into, for example, a flat plate, curved plate, rod, tube, block, etc., by plastic processing such as pressing, punching, cutting, polishing, and thinning processing such as electric discharge processing. In addition, it may be a film-like object such as a metal foil.

[0073] The metal member may have a surface roughened. A known method for roughening the surface may be used, such as (1) immersion in an aggressive aqueous solution or suspension, (2) anodization, or (3) mechanical cutting by blasting or laser processing. Of these, (1) immersion in an aggressive aqueous solution or suspension or (2) anodization is particularly preferred as a method for roughening the surface of a metal member. When the metal member is surface-treated, it is preferred to process the metal member into a desired shape by cutting, plastic processing by pressing, or the like, punching, cutting, grinding, electric discharge machining, or other thinning processing before forming the fine uneven surface.

[0074] A primer layer may be formed on the surface of the metal member that has been subjected to the surface treatment of the metal. The material constituting the primer layer is not particularly limited, but is usually made of a primer resin material containing a resin component. The primer resin material is not particularly limited, and a known material can be used. Specific examples include known polyolefin-based primers, epoxy-based primers, and urethane-based primers. The method of forming the primer layer is not particularly limited, but for example, the primer layer can be formed by applying a solution of the above-mentioned primer resin material or an emulsion of the above-mentioned primer resin material to the metal member that has been subjected to the surface treatment. Examples of the solvent used to prepare the solution include toluene, methyl ethyl ketone (MEK), and dimethyl phosphoramide (DMF). Examples of the medium for the emulsion include an aliphatic hydrocarbon medium and water.

[0075] The method for joining the resin molded article of the present disclosure to the metal member is not particularly limited as long as it does not impair the effects of the present invention, and known methods and devices can be used. For example, there are a method of joining the resin composition of the present disclosure to the metal member by melt molding, a method of welding the molded article of the present disclosure to the metal member, a method of crimping the molded article of the present disclosure to the metal member, and a method of mechanically joining the molded article of the present disclosure to the metal member.

[0076] As a method for joining a metal member by melt molding the resin composition of the present disclosure, a method of insert molding in which a metal member is inserted into a mold of an injection molding machine and then injection molding is performed on the metal member using the resin composition of the present disclosure can be mentioned. The apparatus and manufacturing method in the insert molding method are not particularly limited, and a commercially available apparatus can be used, or the method can be performed according to a conventional method.

[0077] The method of welding the molded article of the present disclosure and the metal member includes contacting the molded article of the present disclosure with the metal member and heating to bond them, or heating and contacting them to bond them and then cooling them.Specific examples of the method include hot plate welding, vibration welding, infrared welding, infrared vibration welding, ultrasonic welding, high frequency welding, induction heating welding, rotary welding, laser welding, hot pressing, hot embossing, and friction stir welding.The apparatus and manufacturing method used in these bonding methods can be commercially available apparatus or can be performed according to a conventional method.

[0078] A method for crimping the molded product of the present disclosure and the metal member includes a method for passing a rivet through a hole in the molded product of the present disclosure and a hole in the metal member, and deforming the rivet to fix them.Specific examples include press crimping, spin crimping, and heat crimping, and the apparatus and manufacturing method used for these joining methods can be commercially available apparatus or can be performed according to conventional methods.A method for mechanically joining the molded product of the present disclosure and the metal member includes a mechanical fastening method using screws, pins, shafts, bolts, nuts, clamps, etc., and fixing with a fitting structure.

[0079] <Application> Since the PAS resin molded article according to the present embodiment has excellent toughness, when it is combined with a metal member or another resin member, it has high adhesion, can reduce the heat and electrical conduction loss at the interface, and furthermore, the interface has excellent long-term stability. Therefore, it is suitable for use as a member that constitutes a composite with a metal member or a resin member. In addition, since the composite according to the present embodiment is characterized by excellent conductivity and long-term stability, it is particularly suitable for conductive parts and electromagnetic shielding parts. Specifically, it can be suitably used for conductive parts such as electrode peripheral parts of lithium ion batteries, carrier trays, battery parts, conductive reels, and conductive pallets, and electromagnetic shielding parts such as electronic device cases, inverter cases, ECU housings, and medical device cases. In addition, the molded article and composite according to the present embodiment can be used not only for conductive parts and electromagnetic shielding parts, but also for ordinary applications such as the following. For example, protective and supporting materials for box-shaped electric and electronic component integrated modules, multiple individual semiconductors or modules, sensors, LED lamps, connectors, sockets, resistors, relay cases, switches, coil bobbins, capacitors, variable capacitor cases, optical pickups, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, power modules, terminal blocks, semiconductors, liquid crystal displays, FDD carriages, FDD chassis, motor brush holders, parabolic antennas, computer-related parts, and other representative electric and electronic parts; VTR parts, television parts, irons, headsets, etc. Home and office electrical appliance parts such as air dryers, rice cooker parts, microwave oven parts, audio parts, audio / visual equipment parts such as laser discs, compact discs, DVD discs, and Blu-ray discs, lighting parts, refrigerator parts, air conditioner parts, typewriter parts, word processor parts, and water-related equipment parts such as water heaters, bath water volume and temperature sensors; office computer related parts, telephone related parts, facsimile related parts, copier related parts, cleaning jigs, motor parts, lighters, typewriters, and other machine related parts; optical equipment and precision machinery related parts such as microscopes, binoculars, cameras, and watches;Alternator terminals, alternator connectors, brush holders, slip rings, IC regulators, potentiometer bases for light dimmers, relay blocks, inhibitor switches, various valves such as exhaust gas valves, various pipes for fuel, exhaust and intake systems, air intake nozzle snorkels, intake manifolds, engine coolant joints, carburetor main bodies, carburetor spacers, exhaust gas sensors, coolant sensors, oil temperature sensors, brake pad wear sensors, throttle position sensors, crankshaft position sensors, temperature sensors, air flow meters, brake pad wear sensors, thermostat bases for air conditioners, heating hot air flow control valves, radiators Examples of automotive and vehicle related parts include brush holders for motors, water pump impellers, turbine vanes, wiper motor related parts, distributors, starter switches, ignition coils and bobbins, motor insulators, motor rotors, motor cores, starter relays, transmission wire harnesses, windshield washer nozzles, air conditioner panel switch boards, coils for fuel-related electromagnetic valves, fuse connectors, horn terminals, electrical component insulating plates, step motor rotors, lamp sockets, lamp reflectors, lamp housings, brake pistons, solenoid bobbins, engine oil filters, ignition device cases, and other various applications. EXAMPLES

[0080] The present invention will be described below using examples and comparative examples, but is not limited to these examples. In the following, unless otherwise specified, "%" and "parts" are based on mass.

[0081] <Examples 1 to 10 and Comparative Examples 1 to 6> Each material was mixed according to the composition and mixing amount shown in Table 1. Then, these mixed materials were fed into a vented twin screw extruder "TEX-30α (product name)" manufactured by Japan Steel Works, Ltd., and melt-kneaded at a resin component discharge rate of 30 kg / hr, a screw rotation speed of 200 rpm, and a set resin temperature of 310°C to obtain pellets of the resin composition. Glass fiber and polyamide fiber were fed from a side feeder (S / T ratio 0.5), and the other materials were mixed uniformly in a tumbler in advance and fed from the top feeder. The pellets of the obtained resin composition were dried in a gear oven at 140°C for 2 hours, and then injection molded to prepare various test pieces, and the following tests were performed.

[0082] <Evaluation>

[0083] (1) Measurement of Charpy impact strength The pellets obtained in each Example and Comparative Example were fed into a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) set at a cylinder temperature of 310°C, and injection molding was performed using an ISO Type 1A dumbbell specimen molding die with the die temperature adjusted to 140°C to obtain ISO Type-A dumbbell specimens. The resin was injected from a single gate so that the test specimens did not include welds. The central portion of the dumbbell-shaped test specimen was cut into a rod shape of 80 mm in length, 10 mm in width, and 4 mm in thickness, and notched to prepare an impact resistance test specimen. A Charpy impact test was performed in accordance with ISO179-1 / 1eA to measure the impact strength (kJ / mm 2 The results are shown in Tables 1 and 2.

[0084] (2) Measurement of bending modulus Using the same ISO Type-A dumbbell specimens as in (1) as test specimens, the flexural modulus (GPa) was measured in accordance with ISO 178. The results are shown in Tables 1 and 2.

[0085] (3) Volume resistivity measurement The volume resistivity was measured using the Loresta AX MCP-T370 manufactured by Nitto Seiko Analytech Co., Ltd. (upper limit of measurement: 10 6The volume resistivity of each test piece was measured at room temperature of 21°C and humidity of 67RH% in accordance with JIS K 7194 "Test method for resistivity of conductive plastics by four-probe method" using a resistivity tester (Ω·cm). The test pieces were prepared by feeding the pellets obtained in each Example and Comparative Example to a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set to 310°C, and injection molding using a plate molding die with a mold temperature controlled to 140°C to form a plate shape (80mm x 50mm x 2mmt). The results are shown in Tables 1 and 2.

[0086] (4) Electrical resistance measurement of molded products The pellets obtained in each Example and Comparative Example were fed to a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set to 310°C, and injection molding was performed using a molding die with a mold temperature controlled to 140°C to obtain a molded product with a length of 20 mm, a width of 40 mm, and a thickness of 1 mm. The obtained molded product was stacked in the thickness direction with two aluminum alloy (A1050) plates of 30 mm x 50 mm x 1 mm, and pressed with a pressure of 30 kPa in a state where the entire molded product was in contact with the aluminum plate. Electrodes were attached to each aluminum alloy plate as it was, and the electrical resistance value (kΩ) when a current of 0.1 mA was applied was measured using a Hioki Electric RM3545 resistance meter. 30 sheets were measured, and the average of the measured resistance values ​​was taken as the electrical resistance value (kΩ) of the molded product, and the standard deviation divided by the average value was evaluated as the variation. The results are shown in Tables 1 and 2.

[0087] (5) Long-term stability evaluation value A molded product similar to that in (4) and an aluminum plate were pressed and fixed at 10 kPa and left to stand for six months in a constant temperature and humidity chamber at 85°C and 95% RH. After leaving the aluminum plate to stand, corrosion products were removed from the aluminum plate using a method using nitric acid as per JIS Z 2371, a method for chemically removing corrosion products. The aluminum plate was then observed with a three-dimensional measuring machine (Keyence VR-6000) and the maximum value of the pit depth on the contact surface with the molded product was measured as the maximum pit depth. The smaller the maximum pit depth, the better the long-term stability. The results are shown in Tables 1 and 2.

[0088] (6) Quantitative determination of carboxyl group content in PAS resin Each PPS resin used in each Example and Comparative Example was pressed at 350°C under a load of 10 MPa for 60 seconds, and then rapidly cooled to 25°C over 60 seconds to prepare a film exhibiting amorphous properties. The obtained film exhibiting amorphous properties was measured using a Fourier transform infrared spectrometer (hereinafter abbreviated as "FT-IR device"). In the infrared absorption spectrum, the peak at 630.6 cm -1 Absorbance at 1705cm -1 The relative intensity of absorbance of was obtained, and the content of carboxyl groups in the measurement sample (hereinafter abbreviated as "total content of carboxyl groups") was obtained using a calibration curve prepared by a method described later. The results are shown in Tables 1 and 2. The content of carboxyl groups is shown in moles per 1 g of resin mixture, and its unit is [μmol / g]. The calibration curve was prepared by the following method. First, a predetermined amount of 4-chlorophenylacetic acid was added to a PAS resin prepared so as to contain a carboxylate at the molecular end without acid treatment, and mixed well. Then, a film similar to the above was prepared and measured with an FT-IR device. A calibration curve was prepared by plotting the relative intensity ratio of absorbance at the two wavelengths against the carboxyl group content calculated from the amount of 4-chlorophenylacetic acid added.

[0089] [Table 1]

[0090] [Table 2]

[0091] The blending ratios of the blended components in Tables 1 and 2 are as follows. ·PPS resin A-1: PPS resin (melt viscosity (V6) 10 Pa·s, zeta potential -58 mV, carboxyl group amount 30 μmol / g) A-2: PPS resin (melt viscosity (V6) 50 Pa·s, zeta potential -64 mV, carboxyl group amount 30 μmol / g) A-3: PPS resin (melt viscosity (V6) 200 Pa·s, zeta potential -63 mV, carboxyl group amount 30 μmol / g) a-4: PPS resin (melt viscosity (V6) 400 Pa·s, zeta potential -60 mV, carboxyl group amount 20 μmol / g)

[0092] Carbon-based materials b-1: Carbon black, Mitsubishi Chemical Corporation "MA-100", pH 3.5, DBP absorption 100 cm 3 / 100g, average primary particle size 24nm B-2: Carbon black, Tokai Carbon Co., Ltd. "#4400", pH 6, DBP absorption 138 cm 3 / 100g, average primary particle size 38nm B-3: Carbon black, "Ketjen Black" manufactured by Lion Specialty Chemicals Co., Ltd., pH 9, DBP absorption 360 cm 3 / 100g, average primary particle size 40nm B-4: Flake graphite, "CNP15" manufactured by Ito Graphite Industries Co., Ltd., pH 8, average particle size 15 μm B-5: Artificial graphite, "AGB-604" manufactured by Ito Graphite Industries Co., Ltd., pH 8, average particle size 55 μm B-6: Expanded graphite, "EC500" manufactured by Ito Graphite Industries Co., Ltd., pH 8, average particle size 25 μm

[0093] C-1: Carbon fiber, Teijin Limited "HT C702", average fiber length 6mm C-2: Glass fiber, Nippon Electric Glass Co., Ltd. "T-717H", fiber length 3 mm, average diameter 10 μm

[0094] D-1: Silane coupling agent, Dow Chemical Company's "XIAMETER(R) OFS-6040" E-1: Thermoplastic elastomer (copolymer of ethylene:methyl acrylate:glycidyl methacrylate = 64 mol%:30 mol%:6 mol%) F-1: Calcium carbonate, Sankyo Flour Milling Co., Ltd. "Calcium carbonate grade 1"

[0095] Comparing the Examples and Comparative Examples in Tables 1 and 2, the molded articles melt-molded from the resin compositions of the Examples were excellent in Charpy impact strength and low in volume resistivity, and the composites of the Examples had small electrical resistance values ​​and variations, and were excellent in long-term stability. Compared to the Examples, Comparative Example 1 had poor long-term stability, Comparative Example 2 had high electrical resistance values, Comparative Example 3 had poor toughness, Comparative Example 4 had poor processability, and Comparative Examples 5 and 6 had large variations in electrical resistance values, and did not meet all the required performances.

Claims

1. A polyarylene sulfide resin composition comprising a polyarylene sulfide resin (A), a carbon-based material other than carbon fiber (B), and a fibrous filler (C) as essential components, The melt viscosity (V6) of the polyarylene sulfide resin (A) is 200 Pa s or less, The pH of the carbon-based material (B) other than the carbon fiber is 6 or more, the blending amount of the carbon-based material (B) other than the carbon fiber is 5 to 80 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A); The carbon-based material (B) other than carbon fiber contains furnace black, The furnace black has a DBP absorption of 100 cm 3 / 100 g or more and a primary particle size of 60 nm or less; the blending amount of the fibrous filler (C) is 20 to 80 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A); and, A polyarylene sulfide resin composition having a flexural modulus of 18 GPa or less. (Note that the melt viscosity (V6) represents the melt viscosity after holding for 6 minutes using a flow tester at a temperature of 300° C., a load of 1.96 MPa, and an orifice with an orifice length to orifice diameter ratio of 10 / 1.)

2. The polyarylene sulfide resin composition according to claim 1, wherein the carbon-based material (B) other than carbon fiber contains graphite having an average particle size of 5 to 400 μm.

3. 3. The polyarylene sulfide resin composition according to claim 1, wherein the polyarylene sulfide resin (A) has a zeta potential of −70 mV or more at pH 7.8 to 8.2 as measured by a streaming potential method.

4. A molded article obtained by melt molding the polyarylene sulfide resin composition according to claim 1 or 2.

5. A composite member obtained by joining the molded article according to claim 4 to a metal member.

6. A secondary battery member comprising the composite member according to claim 5.

7. A method for producing a polyarylene sulfide resin composition, comprising a step of blending a polyarylene sulfide resin (A), a carbon-based material other than carbon fiber (B), and a fibrous filler (C) as essential components, and melt-kneading the blended components at a temperature equal to or higher than the melting point of the polyarylene sulfide resin (A), The melt viscosity (V6) of the polyarylene sulfide resin (A) is 200 Pa s or less, The pH of the carbon-based material (B) other than the carbon fiber is 6 or more, the blending amount of the carbon-based material (B) other than the carbon fiber is 5 to 80 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A); The carbon-based material (B) other than carbon fiber contains furnace black, The furnace black has a DBP absorption of 100 cm 3 / 100 g or more and a primary particle size of 60 nm or less; the blending amount of the fibrous filler (C) is 20 to 80 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A); and, A method for producing a polyarylene sulfide resin composition having a flexural modulus of 18 GPa or less. (Note that the melt viscosity (V6) represents the melt viscosity after holding for 6 minutes using a flow tester at a temperature of 300° C., a load of 1.96 MPa, and an orifice with an orifice length to orifice diameter ratio of 10 / 1.)

8. The method for producing a polyarylene sulfide resin composition according to claim 7, wherein the carbon-based material (B) other than carbon fiber contains graphite having an average particle size of 5 to 400 μm.

9. 9. The method for producing a polyarylene sulfide resin composition according to claim 7 or 8, wherein the polyarylene sulfide resin (A) has a zeta potential of −70 mV or more at pH 7.8 to 8.2 as measured by a streaming potential method.

10. A method for producing a molded article, comprising the steps of producing a polyarylene sulfide resin composition by the method according to claim 7 or 8, and melt-molding the obtained polyarylene sulfide resin composition.

11. A method for producing a composite, comprising the steps of producing a molded article by the method according to claim 10, and joining the obtained molded article to a metal member.

12. A method for using the composite according to claim 6 as a secondary battery member.

Citation Information

Patent Citations

  • Polyarylene sulfide resin composition

    JP1996302189A

  • Polyphenylene sulfide resin composition

    JP2001348478A

  • Thermoplastic resin composition

    JP2007031611A

  • Polyphenylene sulfide-based resin composition and molding or the like comprising the resin composition as base material

    JP2013155288A

  • Method for evaluating polyarylenesulfide resin

    JP2023000930A